Recommendations for the safe, effective use of adaptive CDS in the US healthcare system: an AMIA position paper. (15th January 2021) - Petersen, Carolyn; Smith, Jeffery; Freimuth, Robert R; Goodman, Kenneth W; Jackson, Gretchen Purcell; Kannry, Joseph; Liu, Hongfang; Madhavan, Subha; Sittig, Dean F; Wright, Adam
Abstract: The development and implementation of clinical decision support (CDS) that trains itself and adapts its algorithms based on new data—here referred to as Adaptive CDS—present unique challenges and considerations. Although Adaptive CDS represents an expected progression from earlier work, the activities needed to appropriately manage and support the establishment and evolution of Adaptive CDS require new, coordinated initiatives and oversight that do not currently exist. In this AMIA position paper, the authors describe current and emerging challenges to the safe use of Adaptive CDS and lay out recommendations for the effective management and monitoring of Adaptive CDS.